Análise do ciclo de vida de biocompósitos de bagaço em substituição ao poliestireno expandido em embalagens de delivery - Martins, Nathalia Oliveira (Universidade Federal de São Carlos, 2024)
The delivery market has grown a lot in recent years, accelerated by the restrictions of the COVID-19 pandemic, this style of eating has become a necessity in many people's lives. However, delivery market is still based on the use of packaging made of plastic. These packaging, when discarded incorrectly, can turn into microplastic and end up in the organism of marine animals and even humans. It is in this scenario that studies are emerging to find more sustainable packaging, one of the many possibilities is packaging made from bagasse, which in addition to using a by-product of the sugar and alcohol industry is also biodegradable. This work aims to analyze the life cycle of 1kg of delivery packaging made from two different materials: bagasse and expanded polystyrene (EPS). To calculate the impacts of each chain, the OpenLCA software was used. For the bagasse packaging production flow, it was considered that the raw material would come from a sugar and alcohol industry, subsequently going through a pulp treatment process, heading to the thermoforming industry to generate the packaging and finally having two disposal possibilities: landfill or composting. For EPS packaging, the process begins with the removal of oil, cracking of Naphtha, polymerization and expansion of polystyrene, followed by the thermoforming process and disposal in the landfill. As a result, bagasse performed worse in 7 of the 11 categories studied, with sugarcane cultivation being the main responsible for the values achieved. In relation to disposal in landfill or composting, the impact categories had very similar values to each other, not making the advantage of biodegradable packaging evident.
Life cycle analysis of bagasse biocomposites as a substitute for expanded polystyrene in delivery packaging
Keywords: Avaliação de ciclo de vida; Bagaço; EPS; Embalagens de delivery; Life cycle assessment; Bagasse; Delivery packaging; ENGENHARIAS::ENGENHARIA QUIMICA